EFFECT OF MAGNESIUM SULFATE AND PERSONALISED DIETARY GUIDANCE ON HEMODYNAMICS AND INFLAMMATORY CYTOKINES IN PREGNANCY-INDUCED HYPERTENSION: Hemodynamics and Inflammatory Cytokines in Pregnancy-Induced Hypertension - Shen, Miao; Zhuang, Ying; Zheng, Yaning; Wang, Mengqin; Wang, Jiexun; Lyu, Shuoying (Journal of Medical Biochemistry, 2025)
Introduction: Pregnancy-induced hypertension (PIH) is a significant cause of maternal and neonatal complications, often linked to vascular dysfunction and inflammatory responses. This study aimed to evaluate the effects of magnesium sulfate (MS) combined with personalized dietary guidance on hemodynamic parameters and inflammatory cytokine profiles in PIH patients. Methods: A total of 108 PIH patients were randomly assigned to two groups: a research group (MS and dietary guidance) and a control group (dietary guidance only). Hemodynamic parameters, including systolic and diastolic blood pressure (SBP, DBP), plasma viscosity (PV), and erythrocyte aggregation index (EI), were measured, along with inflammatory cytokines (IL-6, IL-1β, IL-10), before and after treatment. Results: The research group, which received both MS and dietary guidance, showed significant reductions in SBP, DBP, PV, and EI compared to the control group. Additionally, inflammatory cytokines IL-6 and IL-1β were significantly reduced in the research group, indicating an improvement in the inflammatory response. While IL-10 levels decreased in both groups, this change was not statistically significant. Conclusion: The combination of magnesium sulfate and personalized dietary guidance effectively improves hemodynamic stability and reduces inflammatory markers in PIH patients. This intervention may offer beneficial effects for maternal and neonatal health by addressing both hypertension and inflammation associated with PIH.